2022
DOI: 10.1302/0301-620x.104b11.bjj-2022-0470.r2
|View full text |Cite
|
Sign up to set email alerts
|

Significant deterioration in quality of life and increased frailty in patients waiting more than six months for total hip or knee arthroplasty

Abstract: Aims The primary aim of this study was to assess whether patients waiting six months or more for a total hip (THA) or knee (KA) arthroplasty had a deterioration in their health-related quality of life (HRQoL). Secondary aims were to assess changes in frailty and the number of patients living in a state considered to be worse than death (WTD), and factors associated with changes in HRQoL and frailty. Methods This cross-sectional study included 326 patients, 150 males (46.0%) and 176 females (54.0%), with a mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 45 publications
(82 reference statements)
0
17
0
Order By: Relevance
“…It should also be noted that our use of the EQ-5D-5L, which differs from contemporary studies that have used EQ-5D-3L scores, 2,3,15,22 does have implications. The EQ-5D-5L descriptive set was developed to provide more precise measurements than the EQ-5D-3L at individual and group levels, 23 and comparative studies have suggested that it has stronger validity for patients awaiting THA and TKA.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…It should also be noted that our use of the EQ-5D-5L, which differs from contemporary studies that have used EQ-5D-3L scores, 2,3,15,22 does have implications. The EQ-5D-5L descriptive set was developed to provide more precise measurements than the EQ-5D-3L at individual and group levels, 23 and comparative studies have suggested that it has stronger validity for patients awaiting THA and TKA.…”
Section: Discussionmentioning
confidence: 89%
“… 14 Likewise, cross-sectional studies of patients awaiting lower limb arthroplasty at various orthopaedic departments across the UK have revealed a similar trend, where individuals awaiting THA are significantly more likely to be in a health state WTD. 2 , 15 It was also found that each additional six months of waiting for lower limb arthroplasty corresponds with a clinically significant deterioration in EQ-5D-3L score.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This is becoming normal for some patients in the UK, and this research group from Edinburgh (UK) have added to some of the previous work carried out in the region, which demonstrated that waiting for arthroplasty surgery can lead to a physical state that was worse than death, and have demonstrated some of the effects that waiting for arthroplasty surgery can have on a patient's general health. 2 A randomly selected group of 326 patients from multiple hospitals were included in the study who had been waiting for six months or more for surgery. These patients were sent questionnaires, the results of which were compared to results that had been obtained six months earlier.…”
Section: Signifi Cant Deterioration In Quality Of Life and Increased ...mentioning
confidence: 99%